Pasture Renovation - Carrol G. Chambliss (EDIS)
This document is SS-AGR-174, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. This publication is also part of the Florida Forage Handbook, an electronic publication of the Agronomy Department. First Published August 2002.